Inclusive Education in Indian Context - Bindal, Shivani; Sharma, Sushma (JOURNAL OF INDIAN EDUCATION, 2010)
Inclusive education lays the foundation to an inclusive society accepting, respecting and celebrating diversity. The present paper traces the concept of inclusive education in Indian context. The paper throws light on the International and National level Policy frameworks and Legislations in inclusive education. The paper critically reviews need of inclusive education in India and role of schools in inclusive education.